972. Bone and Joint Infections : Looking Beyond Gram Positive Bugs, A Case Series from Mumbai, India. (15th December 2022) - Kaneria, Mala V; Kothari, Manish; Vishwanath, Jashan; Jain, Reetu; Raut, Indraneel; Mashru, Puneet; Gohel, Tejash; Bhabhor, Anand; Nagral, Aabha; Wadia, Pettarusp; Savardekar, Abhijeet; Pispati, Ameet; et al.
Abstract: Background: Bone and joint infection (BJI) is a dreadful complication of arthroplasties and orthopaedic trauma. Infection with non traditional organisms is a trade off for medical advances such as newer immunosuppressants and implants. Complex BJIs, may be complicated by longer hospitalizations and higher costs due to the virulence of organisms, growing resistance to antibiotics and patient comorbidities, especially immunocompromised status. The purpose of this study was to analyse the various characteristics of BJIs with emphasis on the organisms cultured. Methods: 21 consecutive patients of BJIs were prospectively included from June 2021 to March 2022. Demographic features, comorbidities, anatomic site involved, previous surgical intervention, presence of implant, infecting organism, their susceptibility patterns, inflammatory markers, surgical procedure performed, antibiotics given, their route, duration and the outcome were noted. Results: 12/21 (57.14 %) had spondylodiscitis ; 4/21 (19.04 %) knee joint involvement ; 3/21 (14.29 %) orthopaedic trauma ; 3/21 (14.29 %) hip involvement ; 1 ankle joint involvement (diabetic foot) and 1 sternal osteomyelitis. 17/21 (80.95 %) had comorbidities. 7/21 (33.33 %) were immunosuppressed . 14/21 (66.67 %) had undergone recent surgery. 11 gram positive, 8 gram negative organisms and 3 fungi were isolated . 2 were culture negative and 4 had mycobacterial infection. Histopathology revealed pyogenic inflammation in bacterial and granulomatous inflammation in fungal and mycobacterial infections. CRP and ESR were elevated in all bacterial infections and were used to guide antibiotic route switchover. All bacterial infections were treated with 6 weeks of antibiotics .14/21 (66.67 %) underwent surgery, whereas the rest underwent diagnostic aspiration and biopsy only. 3/21 (14.29 %) had relapse on stopping antibiotics and responded after restarting. Conclusion: Though staphylococcus is thought to be the culprit in most cases of BJIs, gram negative organisms, mycobacteria and fungi are gaining centrestage. Histopathology can give important clues in the absence of positive cultures. Surgical interventions, implant presence and immunosuppressed states are implicated in a majority of the infections. CRP guided therapy is a valuable strategy. Disclosures: All Authors : No reported disclosures.